A systematic synthesis of qualitative studies on parents’ experiences of participating in early intervention programs with their infant born preterm - Øberg, Gunn Kristin; Sørvoll, Marit; Labori, Cathrine; Girolami, Gay L.; Håkstad, Ragnhild B. (Frontiers in Psychology, 2023)
Early intervention programs involving both the parent and the infant born preterm have demonstrated positive effects on developmental outcomes for the children. However, studies have also shown that parental engagement and adherence when implementing intervention programs can be challenging. The aim of this review was to provide a comprehensive description and new insights into key messages gleaned from the parent reports on participating in early intervention with their infant born preterm; knowledge vital to facilitate implementation of early interventions into clinical practice when using a model of direct parent involvement. Early intervention is broadly defined as a multi-interdisciplinary field provided to children from birth to five years of age to foster child health, wellbeing, development, adapting parenting and family function. For this systematic synthesis we define early intervention as programs with specific activities completed with the infant during the first year after birth. We assembled qualitative interview studies on parents’ experiences with participation in early intervention and applied Malterud’s qualitative systematic meta-synthesis to synthesize and translate the original findings across studies. In the analysis we applied enactive concepts of embodiment, autonomy, participatory sensemaking, and agency. 10 qualitative studies were identified and included. The systematic synthesis reveals how parents’ successful and meaningful participation in early intervention programs were facilitated by their “active embodied doing.” The “embodied doing” appeared as the basis for the parents’ sense-making processes, development of confidence, and the ability for parents to see new possibilities for actions within themselves, with and in the child. In that respect, a perception of mutuality in the interaction between parent, infant and interventionist was central. Consequently, an important consideration when implementing early intervention into clinical practice is to promote embodied parent–infant interactions as well as trust between the parent and the interventionist.